ALAT PENGUKUR DETAK JANTUNG MENGGUNAKAN PULSESENSOR BERBASIS ARDUINO UNO R3 YANG DIINTEGRASIKAN DENGAN BLUETOOTH - Wohingati, Galuh Wahyu; Subari, Arkhan (Gema Teknologi, 2013)
Galuh Wahyu Wohingati, Arkhan Subari, in paper pulse measuring tool using pulsesensor based on Arduino Uno R3 integrated with Bluetooth explain that emerging disease and claimed the lives of many people is often due to late treatment , when it should be in the modern era has many tools made to overcome this problem , medical devices can only be used by medical experts , and of course takes time and no small cost . as well as heart disease which sometimes can only be detected when it is advanced because of the lack of monitoring , both from people who are sick or from a doctor . Other factors that cause costs adalahkesibukan and not everyone can do medical check- ups regularly . Whereas By knowing the health condition of a person's heart rate will then be awake , do not need expensive care from a doctor , but could by changing lifestyle . Therefore it needs to be made a tool that can measure heart rate , showing whether or not the condition of the heart and of course, this tool can be used by everyone without kecuali.Dengan development of technology and the number of components on the market which can be accessed , Arduino Uno facilities in R3 can be used . Arduino is a physical computing platform that is open source means , Arduino can be developed by many people , not just programmers .But not just a development tool , Arduino is a combination of hardware , programming language and integrated development environment ( IDE ) that is advanced . Paired with a pulse sensor , a media reader analog heart rate is then converted into digital data that is in the readings , then integrated using serial bluetoothsecara so it can be displayed on your android smartphone and used repeatedly as needed measurements .. Keywords : Arduino Uno R3 , pulse sensor , Bluetooth